2011
DOI: 10.1590/s0103-507x2011000400009
|View full text |Cite
|
Sign up to set email alerts
|

Terminalidade da vida em terapia intensiva: posicionamento dos familiares sobre ortotanásia

Abstract: Objectives: This study aimed to assess family member acceptance of orthotanasia as related to symptom management, patient preference and the influence of the medical team's communication on therapy. Methods: This was a descriptive one-year study conducted at the adult intensive care unit of the Hospital do Servidor Público Estadual. A structured questionnaire based on the Quality of Dying and Death (QODD 22) instrument and prior informal interviews were used. Results: Sixty family members were assessed; the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
0
12
0
2
Order By: Relevance
“…Although the norm authorizes the suspension, in the second speech, only non-instituted therapies are mentioned: no hemodialysis institution; no increase in the flow of vasoactive drugs; and no cardiopulmonary resuscitation. Another study has already observed the same therapies cited by the interviewees as less established 8 …”
Section: : Limiting Is Not Instituting Useless Therapy To a Termimentioning
confidence: 85%
See 1 more Smart Citation
“…Although the norm authorizes the suspension, in the second speech, only non-instituted therapies are mentioned: no hemodialysis institution; no increase in the flow of vasoactive drugs; and no cardiopulmonary resuscitation. Another study has already observed the same therapies cited by the interviewees as less established 8 …”
Section: : Limiting Is Not Instituting Useless Therapy To a Termimentioning
confidence: 85%
“…This aspect is related to the history of life, culture, ideology, myths, among others. It is extremely important to know these factors, which should help understand what families think about LSL 8 .…”
Section: : It Is Necessary To Understand the Family And My Role Imentioning
confidence: 99%
“…These results point to the difficulty of physicians to accept their limitations as "healers" and also as communicators in situations of conflict [41][42][43][44] . It should be emphasized that physicians' fear of legal proceedings directly interferes with end-of-life decisions.…”
Section: Marques Filho and Hossnementioning
confidence: 99%
“…Aspectos considerados importantes no processo comunicacional são citados pelos entrevistados, como o fornecimento de informações claras, honestas e realistas; o respeito às emoções e sentimentos suscitados por esta situação; ter boa capacidade de ouvir; evitar excessos no uso da linguagem técnica e do jargão médico e ter tempo e disponibilidade para conversar com a família sempre que esta demandar atenção ou apresentar dúvidas (SOARES, 2007;SCHAEFER & BLOCK, 2009;SANTOS & BASSITT, 2011;SLEEMAN & COLLIS, 2013). Sobre este último aspecto, a médica 6 aponta uma dificuldade -a impossibilidade de estar disponível sempre que a família demandar.…”
Section: Comunicando Más Notíciasunclassified
“…O prognóstico deve ser informado para dar tempo para a família se preparar e dizer adeus a seu ente querido. Uma comunicação empática, efetiva e afetiva com as famílias de pacientes em situação de terminalidade pressupõe também que os médicos tenham tempo e disponibilidade para conversar com os familiares sempre que estes demandarem atenção ou apresentarem dúvidas, e que tenham boa capacidade de escuta (SOARES, 2007;SCHAEFER & BLOCK, 2009;NELSON et al, 2010;SANTOS & BASSITT, 2011;SLEEMAN & COLLIS, 2013 O cuidado e o amparo fornecidos pelos médicos-assistentes em nossa pesquisa foram fundamentais para que os familiares entrevistados pudessem se preparar para a morte de seu familiar, mesmo sendo uma experiência penosa, dolorosa e adversa. Entretanto, encontramos também a percepção de que a comunicação foi deficitária, pela falta de clareza, de objetividade e de preparo emocional dos médicos.…”
Section: Relação Com a Equipe Médicaunclassified